Reduction of membrane fouling using a helical baffle for cross flow microfiltration - Ahmad, A. L.; Mariadas, A.; Zulkali, M. M. D. (2004)
The introduction of turbulence promoters such as helical baffles were shown to enhance permeate flux during crossflow microfiltration. Helical inserts reduce hold-up in the feed channel; increase fluid velocity and wall shear rates and produce secondary flows or instabilities. The aim of this work was to investigate the influence of helical baffles on permeate flux during the microfiltration of titanium dioxide (TiO2) dispersions and bakers yeast solutions. Tubular, single channel ceramic membranes with nominal pore size of 0.2Âµm were used. Variations of the helical baffle geometries, which are the number of turns per baffle length, were investigated. It is found that the insertion of helical baffles increased the permeate flux. In some cases, the increase was more than 100%. The effect of number of turns per baffle length shows that the permeate flux increases with the number of turns but decreases when the number of turns is more than 4 turns per 50 mm baffle length. Thus, the optimum number of turn is 4 turns per 50mm.